The multiple and versatile roles of Aureobasidium pullulans in the vitivinicultural sector - Bozoudi, Despina; Tsaltas, Dimitrios (My University, 2018)
The saprophytic yeast-like fungus Aureobasidium pullulans has been well documented for over 60 years in the microbiological literature. It is ubiquitous in distribution, being found in a variety of environments (plant surfaces, soil, water, rock surfaces and manmade surfaces), and with a worldwide distribution from cold to warm climates and wet/humid regions to arid ones. Isolates and strains of A. pullulans produce a wide range of natural products well documented in the international literature and which have been regarded as safe for biotechnological and environmental applications. Showing antagonistic activity against plant pathogens (especially post-harvest pathogens) is one of the major applications currently in agriculture of the fungus, with nutrient and space competition, production of volatile organic compounds, and production of hydrolytic enzymes and antimicrobial compounds (antibacterial and antifungal). The fungus also shows a positive role on mycotoxin biocontrol through various modes, with the most striking being that of binding and/or absorption. A. pullulans strains have been reported to produce very useful industrial enzymes, such as β-glucosidase, amylases, cellulases, lipases, proteases, xylanases and mannanases. Pullulan (poly-α-1,6-maltotriose biopolymer) is an A. pullulans trademark product with significant properties and biotechnological applications in the food, cosmetic and pharmaceutical industries. Poly (β-L-malic acid), or PMA, which is a natural biopolyester, and liamocins, a group of produced heavy oils and siderophores, are among other valuable compounds detected that are of possible biotechnological use. The fungus also shows a potential single-cell protein source capacity with high levels of nucleic acid components and essential amino acids, but this remains to be further explored. Last but not least, the fungus has shown very good biocontrol against aerial plant pathogens. All these properties are of major interest in the vitivinicultural sector and are thoroughly reviewed under this prism, concluding on the importance that A. pullulans may have if used at both vineyard and winery levels. This extensive array of properties provides excellent tools for the viticulturist/farmer as well as for the oenologist to combat problems in the field and create a high-quality wine.
Keywords: Aureobasidium pullulans; Biotechnological applications; Enzymes; Non-Saccharomyces yeasts; Viticulture